2015
DOI: 10.1007/s11292-015-9236-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of tailored interventions for health promotion and recidivism reduction among homeless parolees: outcomes and cost analysis

Abstract: Objectives This study conducted a randomized controlled trial with 600 recently released homeless men exiting California jails and prisons. Methods The purpose of this study was to primarily ascertain how different levels of intensity in peer coaching and nurse-partnered intervention programs may impact reentry outcomes; specifically: (a) an intensive peer coach and nurse case managed (PC-NCM) program; (b) an intermediate peer coaching (PC) program with brief nurse counseling; and (c) the usual care (UC) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(65 citation statements)
references
References 55 publications
0
64
0
1
Order By: Relevance
“…Evidence on cost and cost-effectiveness was mixed. The total cost incurred by SCM clients was higher than those receiving usual or standard care [50,79], but lower compared to a US clinical case management program that included housing vouchers and ICM [98]. Cost-effectiveness studies showed that when the benefits gained and costs borne to all payers were considered (also known as a societal perspective) SCM was not cost-effective compared to ACT for persons with serious mental disorders or those with a concurrent substance-use disorder as it was both more expensive [56,94], and was associated with more days in unstable housing [56], and poorer quality of life [94].…”
Section: Cost and Cost-effectiveness Of The Interventionsmentioning
confidence: 86%
See 3 more Smart Citations
“…Evidence on cost and cost-effectiveness was mixed. The total cost incurred by SCM clients was higher than those receiving usual or standard care [50,79], but lower compared to a US clinical case management program that included housing vouchers and ICM [98]. Cost-effectiveness studies showed that when the benefits gained and costs borne to all payers were considered (also known as a societal perspective) SCM was not cost-effective compared to ACT for persons with serious mental disorders or those with a concurrent substance-use disorder as it was both more expensive [56,94], and was associated with more days in unstable housing [56], and poorer quality of life [94].…”
Section: Cost and Cost-effectiveness Of The Interventionsmentioning
confidence: 86%
“…Two additional trials reported no impact on mental health outcomes [44,54]. Two trials reported decreased problematic substance use [44,79], and four others reported no effect on this outcome [48][49][50]53].…”
Section: Effects Of Standard Case Management (Scm)mentioning
confidence: 95%
See 2 more Smart Citations
“…Twelve publications provided evidence on cost and costeffectiveness of case-management interventions. 44,55,67,69,73,75,88,96,[147][148][149][150] Findings of these studies were mixed; the total cost incurred by clients of standard case management was higher than that of clients receiving usual or standard care 61,88 and assertive commun ity treatment, 67,147 but lower compared with a US clinical case-management program that included housing vouchers and intensive case management. 55 Cost-effectiveness studies using a societal perspective showed that standard case management was not cost effective compared with assertive community treatment for people with serious mental disorders or those with a concurrent substance-use disorder, as it was more expensive.…”
Section: Case Managementmentioning
confidence: 99%